(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
Stratigraphic and sedimentologic studies of the Anisian sediments outcropping in North West Friuli allowed the reinterpretation of the stratigraphic sequence and the reconstruction of the paleogeographic and structural evolution of this area.